Virtual Class for Sunday School Teachers During the Covid-19 Pandemic - Daniel Ginting; Ratri Kusuma Wijaya; Roike Roudjer Kowal (Jurnal Pendidikan Agama Kristen (JUPAK), 2022)
Sunday School programs play an important role in promoting the spiritual growth of children. Educating children is a must. Children are God's inheritance to parents. Conducting ministry to children has been started since the Old Testament times as God commanded Moses (Exodus 12:25-27). Today, the COVID-19 pandemic has forced Sunday School teachers to adapt to technology. In the perspective of the cognitive load theory of multimedia-based learning, the media is a central factor determining the successful attainment of learning objectives. Effective media makes learning easy that enables the Sunday School students to process and integrate new information with their prior knowledge. In so doing, the reconstruction of new knowledge during the learning process via multimedia is possibly generated. However, the extent to which Sunday school teachers can make use of technology in the context of Sunday School teaching has not extensively been explored in the pandemic studies. This paper aims to provide a sketch of the implementation of teaching and learning activities carried out by Sunday school teachers at church X during the pandemic. About eight Sunday school teachers are involved as the subjects of this study: one male Sunday school teacher (12%) and seven female Sunday school teachers (88%). This paper finds that Sunday School teachers can adapt to technology. To design an effective teaching media, the teachers minimize extrinsic load to promote effective learning while maintaining appropriate difficulty level of the new topics being presented (intrinsic load).